2017
DOI: 10.3390/molecules22081387
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Two Iridoid Synthase Homologs from Swertia Mussotii

Abstract: Swertia mussotii is an important medicinal plant found on the Qinghai Tibetan Plateau that has great economic and medicinal value. This plant has enjoyed a long history of use as a curative for hepatitis. The biological activity of secoiridoids, including gentiopicroside and swertiamarin, has been mainly tested for its anti-hepatitis effects. Here, we identify two candidate genes (SmIS1 and SmIS2) that are homologues of iridoid synthase and that are components of the secoiridoid pathway in S. mussotii. Using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…As both PRISEss ( Nr PRISE2 and Nn PRISE) resulted in the production of cis,trans -nepetalactol in the absence of NEPSs, our results indicate that cyclization occurred spontaneously. This was also confirmed for Nc ISY2 and Nm ISY2 ( Sherden et al., 2017 ), as well as for ISYs from plants of other genera ( Geu-Flores et al., 2012 ; Alagna et al., 2016 ; Kries et al., 2017 ; Xiang et al., 2017 ; Fellows et al., 2018 ).…”
Section: Resultssupporting
confidence: 64%
“…As both PRISEss ( Nr PRISE2 and Nn PRISE) resulted in the production of cis,trans -nepetalactol in the absence of NEPSs, our results indicate that cyclization occurred spontaneously. This was also confirmed for Nc ISY2 and Nm ISY2 ( Sherden et al., 2017 ), as well as for ISYs from plants of other genera ( Geu-Flores et al., 2012 ; Alagna et al., 2016 ; Kries et al., 2017 ; Xiang et al., 2017 ; Fellows et al., 2018 ).…”
Section: Resultssupporting
confidence: 64%
“…In this study, our sequence and structural analysis, site‐directed mutagenesis and MD simulations (based on the available structures of IS) have shown that two residues, Glu161 and Gly162, of the loop L1 and Asn358 residue at L2 determine the substrate specificity of the enzymes. Recently, iridoid synthases and their isoforms from other plant sources such as Swertia Mussotii (SmSI1 & SmSI2) , Olea europaea L. (OeISY, Oe1,4‐R1, Oe1,4‐R2 & Oe1,4‐R3) , and Antirrhinum majus (AmISY) have been characterized for their reductase activity. Interestingly, some of these enzymes exhibit differential specificity toward 10‐oxogeranial and progesterone (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Two candidate genes, SmIS1 and SmIS2 that belong to the P5βR group as homologs of IS were isolated from S. mussotii , and the E. coli ‐expressed proteins encoded by these two genes were able to reduce 8‐oxogeranial to nepetalactol and iridodials (Scheme 1). 224 Moreover, the transcript levels of SmIS1 and SmIS2 were more abundant in the leaves and stems than other tissues when measured by semi‐quantitative RT‐PCR and RT‐qPCR.…”
Section: Biosynthesis and Synthesis Of Secoiridoidsmentioning
confidence: 94%
“…124,171,144,200,207,[223][224][225][226][227] were evaluated for their anti-HBV activity on HepG 2.2.15 cell line in vitro,88,94,100,127,129,130 namely inhibiting the secretions of hepatitis B surface antigen (HBsAg), hepatitis Beantigen (HBeAg), and hepatitis B virus (HBV) DNA replication, among which 9-epi swertiamarin 115, swericinctosides A 124, swertiakoulactone 144, 4′-O-acetyl swertianoside E 171, and swertianosides A 200 showed inhibitory effects on secretion of HBsAg, 200 showed significant activities inhibiting the secretion of HBeAg, and 115, 124, 144, 207, and 223-227 could inhibit HBV DNA replication.…”
mentioning
confidence: 99%